2021
DOI: 10.1039/d0cy02189j
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-catalytic ammonia synthesis beyond thermal equilibrium on Ru-based catalysts in non-thermal plasma

Abstract: Mehta et al. 1 proposed that plasma-catalytic NH3 synthesis with excited N2 allows for conversions beyond thermal equilibrium. We show that this is indeed possible with experimental data for Ru-based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 62 publications
3
88
0
Order By: Relevance
“…Of course, the yield and the concentration of NH 3 are directly related as shown in Equations ( 4) and (7). While other works report lower EC values, the respective NH 3 yields are often also very low (from <0.1 to 0.7%) and correspond to similarly low values of NH 3 concentrations (<1 vol%), as seen e.g., in [18,35,46,56] In our previous work, we demonstrated that a process of NH 3 production becomes plausible only if the NH 3 concentration in the reaction mixture is ≥1 vol% due to the 'hidden' additional energy costs required for product separation [16]. In this regard, our value of ca.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Of course, the yield and the concentration of NH 3 are directly related as shown in Equations ( 4) and (7). While other works report lower EC values, the respective NH 3 yields are often also very low (from <0.1 to 0.7%) and correspond to similarly low values of NH 3 concentrations (<1 vol%), as seen e.g., in [18,35,46,56] In our previous work, we demonstrated that a process of NH 3 production becomes plausible only if the NH 3 concentration in the reaction mixture is ≥1 vol% due to the 'hidden' additional energy costs required for product separation [16]. In this regard, our value of ca.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, different pathways leading from N 2 to NH 3 were investigated. Among these are reduction of the plasma-produced NO x to NH 3 [16,17], and direct reactions of N 2 with H 2 [18,19] or H 2 O [20][21][22], as also summarised in detail in recent reviews [23,24]. We show the possible pathways of the plasma-driven N 2 fixation in Figure 1.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Thus, process development has been the focus of the recent studies with H 2 generated electrochemically from water and then combined with N 2 in a conventional NH 3 synthesis process. , Plasma N 2 fixation into NH 3 , on the other hand, recently enjoyed a rejuvenation. Cold dielectric discharge barrier (DBD) plasma-enhanced catalytic NH 3 synthesis from N 2 and H 2 has been shown to take place at near room temperatures. For example, an NH 3 synthesis rate of 471 μmol g –1 h –1 was reported recently using Ni/Al 2 O 3 as a catalyst with DBD plasma and significant work is currently taking place on exploring the DBD plasma-assisted catalytic NH 3 reaction , including elucidating the underlying mechanisms and reactive intermediates. However, it is not yet clear whether plasma-based NH 3 synthesis will be the most feasible alternative for either centralized or decentralized ammonia production . This is due to the lack of process-wide models where integration of plasma reactors into the existing gas infrastructure can be assessed.…”
Section: Introductionmentioning
confidence: 99%